Respuesta :

Answer: C

Step-by-step explanation:

For this problem, let's find the inverse for all f(x) and see which pairs with the g(x). To find the inverse, you replace the x with y and y with x. Then you solve for y.

A. Incorrect

[tex]y=\frac{x-8}{4} +9[/tex]                                 [replace x with y and y with x]

[tex]x=\frac{y-8}{4} +9[/tex]                                  [subtract both sides by 9]

[tex]x-9=\frac{y-8}{4}[/tex]                                  [multiply both sides by 4]

[tex]4(x-9)=y-8[/tex]                            [add both sides by 8]

[tex]4(x-9)+8=y[/tex]

This does not match g(x), therefore, they are not inverses of each other.

----------------------------------------------------------------------------------------------------------

B. Incorrect

[tex]y=4(x-12)+2[/tex]                         [replace x with y and y with x]

[tex]x=4(y-12)+2[/tex]                         [subtract both sides by 2]

[tex]x-2=4(y-12)[/tex]                        [divide both sides by 4]

[tex]\frac{x-2}{4} =y-12[/tex]                                [add both sides by 12]

[tex]\frac{x-2}{4} +12=y[/tex]

This does not match g(x), therefore, they are not inverses of each other.

----------------------------------------------------------------------------------------------------------

C. Correct

[tex]y=3(\frac{x}{2})-4[/tex]                                [replace x with y and y with x]

[tex]x=3(\frac{y}{2} )-4[/tex]                                [add both sides by 4]

[tex]x+4=3(\frac{y}{2} )[/tex]                                [divide both sides by 3]

[tex]\frac{x+4}{3} =\frac{y}{2}[/tex]                                       [multiply both sides by 2]

[tex]\frac{2(x+4)}{3} =y[/tex]

This matches g(x), therefore, they are inverses of each other.

----------------------------------------------------------------------------------------------------------

D. Incorrect

[tex]y=3(\frac{2}{x} )-10[/tex]                             [replace x with y and y with x]

[tex]x=3(\frac{2}{y} )-10[/tex]                             [add both sides by 10]

[tex]x+10=3(\frac{2}{y} )[/tex]                              [divide both sides by 3]

[tex]\frac{x+10}{3} =\frac{2}{y}[/tex]                                     [multiply both sides by y]

[tex](y)(\frac{x+10}{3} )=2[/tex]                              [multiply both sides by [tex]\frac{3}{x+10}[/tex] or divide by [tex]\frac{x+10}{3}[/tex]]

[tex]y=\frac{6}{x+10}[/tex]

This does not match g(x), therefore, they are not inverses of each other.

----------------------------------------------------------------------------------------------------------

After going through each problem, we found that the correct answer is C.